Interregional Migration in Romania during the 1990s - Daniela-Luminita Constantin; Cornelia Parlog; Zizi Goschin (European Regional Science Association (ERSA), 2003)
Since 1990 the territorial mobility in Romania has recorded a series of particularities determined by major transformations in the political, economic and social life. The economic disparities already existing between the prosperous and the lagging regions have increased during the transition years, influenced by institutional renewal, restructuring, privatization, etc. Several regions display higher unemployment rates, lower activity rates, lower incomes per capita and higher out-migration rates compared with the average. These regions have adapted inadequately to the changing economic conditions, such as the decline of various industries (e.g. coal mining in the south part of Romania) and, as a result of this fact, their out-migration has been intensified. In the early 1990s were already noticed widespread regional disparities in terms of labour supply as well as the main demographic indicators. Starting from this overall image the present paper examines the main changes in the intensity, orientation and territorial distance of migration flows as well as their structure and the variable influence of the ?push / pull? factors involved in this process. As a preliminary step in the analysis of the main characteristics of interregional mobility in Romania, the most significant zones in terms of their contribution to total national migration have been selected. Population and labour mobility between regions has been studied using a set of indicators calculated for the 1990 - 2000 period: gross and net migration, in- and out-migration rates, in- and out-migration flows for the selected zones, their structure and dynamics and so on. Regression functions, input-output tables and gravitational models have been mainly employed. Analysing the results, the economic disparities seem to be the key issue in the question of population and labour mobility, as asserted by the neoclassical theory. Though, its mechanism is not confirmed by a series of concrete situations, such as the intense urban-rural flows, showing that, besides the economic factors, the institutional ones as well as the individual and family motivations are also very important for the persons that decide to migrate. In the next years is expected a decrease in the interregional migration in favour of the intra-regional one. The migration flows from urban to rural areas at the same time with those from rural to rural areas will continue to play a significant role. Finally, the paper discusses the economic policy measures able to reduce the long-distance migration and the intensity of the ?push? factors.
Keywords: 330